Quality of life of women during in vitro fertilization process - Rodić Ana; Malenković Goran; Bjelica Artur; Tomić Sanja; Tomić Slobodan (Association of Nurses Technicians and Midwives, 2022)
Introduction: Infertility is a very important medical and social problem that affects increasing number of couples. Taking into account the specifics of the problem, impact on the partnership and social interactions, treatment of infertility can have significant negative impacts on the quality of life in women during the in-vitrofertilization procedure (IVF). Main goal: To determine the quality of life of women during the IVF process in relation to general life satisfaction, physical and mental health, as well as to determine the satisfaction of patients with health services during the IVF process. Material and methods: The research was conducted as a descriptive cross-sectional study lasting 4 months. The survey was conducted online, the sample consisted of 150 respondents currently in the IVF process. The Fertility quality of life tool questionnaire - FertiQol - was used as a data collection tool. Results: The largest number of respondents are in good general physical condition (61.5%) and are satisfied with the general quality of their life (67.7%). Significant statistical differences were proved between the score Core Quality of life and the score Quality of life in the treatment domain (p<0,001). These results show that the respondents' core quality of life is statistically significantly higher than the quality of life associated with in vitro fertilization. Conclusion: The research confirmed that patients entering the IVF process are satisfied with the overall quality of life, but have a lower quality of life compared to their core, which is directly related to the lack of necessary information that is not available at the optimal time and/or presented in an adequate way, as well as the level of communication with health professionals that needs to be improved.